2013
DOI: 10.1080/09205063.2013.843966
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic support based on dendritic poly(L-lysine) improves human skin fibroblasts attachment

Abstract: Poly(L-lysine) (PLL) dendrigrafts (DGLs) are arborescent biosynthetic polymers of regular and controlled structures. They have specific properties such as biocompatibility and non-immunogenicity, and their surface density of NH2 functions can be easily modified and therefore appears as a powerful tool for the functionalization of hydrophobic polymers used in the context of tissue engineering. In this study, we evaluated several criteria of human skin fibroblasts when cultured with DGL of generations 2, 3 and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…Our results revealed that coating with dendrigraft polylysine of higher generations provided better surface for nerve cell adhesion than linear polylysine, although the adsorption to the PGA fibers was less and unstable. It was previously reported that dendrigraft polylysine conjugation to cell substrates was more effective for promoting the adhesion of fibroblasts than linear polylysine, and that the coated dendrigraft polylysine was released from the substrate . These results are consistent with the results obtained in our study.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results revealed that coating with dendrigraft polylysine of higher generations provided better surface for nerve cell adhesion than linear polylysine, although the adsorption to the PGA fibers was less and unstable. It was previously reported that dendrigraft polylysine conjugation to cell substrates was more effective for promoting the adhesion of fibroblasts than linear polylysine, and that the coated dendrigraft polylysine was released from the substrate . These results are consistent with the results obtained in our study.…”
Section: Discussionsupporting
confidence: 93%
“…It was previously reported that dendrigraft polylysine conjugation to cell substrates was more effective for promoting the adhesion of fibroblasts than linear polylysine, and that the coated dendrigraft polylysine was released from the substrate. [21][22][23] These results are consistent with the results obtained in our study. Lu et al reported that cell adhesion increased by polymer mixing as well as polymer coating.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…[26] It turned out that the interactions of anionic ATPm olecules on the surfaces were identicalt ot hat of the free DGL in solution in term of stoichiometry,s howing that the immobilization procedure does not alter the binding properties of the dendritic polymer.U nmodified DLGs can also be attached on as olid support by using reactive polystyrene that bearsepoxy functionalities. [27] For both approaches, AFM studies revealed that the resulting nanomaterials displayed monolayered homogeneous surfaces.…”
Section: Functionalizationa Nd Immobilizationmentioning
confidence: 99%